Tea Polyphenols Inhibit Rat Osteoclast Formation and Differentiation - Yoshiomi Oka; Shinichi Iwai; Hitoshi Amano; Yuko Irie; Kentaro Yatomi; Kakei Ryu; Shoji Yamada; Katsunori Inagaki; Katsuji Oguchi (Elsevier, 2012)
Matrix metalloproteinases (MMPs) play an important role in degeneration of the matrix associated with bone and cartilage. Regulation of osteoclast activity is essential in the treatment of bone disease, including osteoporosis and rheumatoid arthritis. Polyphenols in green tea, particularly epigallocatechin-3-gallate (EGCG), inhibit MMPs expression and activity. However, the effects of the black tea polyphenol, theaflavin-3,3'-digallate (TFDG), on osteoclast and MMP activity are unknown. Therefore, we examined whether TFDG and EGCG affect MMP activity and osteoclast formation and differentiation in vitro. TFDG or EGCG (10 and 100 μM) was added to cultures of rat osteoclast precursors cells and mature osteoclasts. Numbers of multinucleated osteoclasts and actin rings decreased in polyphenol-treated cultures relative to control cultures. MMP-2 and MMP-9 activities were lower in TFDG- and EGCG-treated rat osteoclast precursor cells than in control cultures. MMP-9 mRNA levels declined significantly in TFDG-treated osteoclasts in comparison to control osteoclasts. TFDG and EGCG inhibited the formation and differentiation of osteoclasts via inhibition of MMPs. TFDG may suppress actin ring formation more effectively than EGCG. Thus, TFDG and EGCG may be suitable agents or lead compounds for the treatment of bone resorption diseases. Keywords:: theaflavin-3,3'-digallate (TFDG), epigallocatechin-3-gallate (EGCG), rat osteoclast, rat osteoclast precursor cell, matrix metalloproteinase (MMP)-9